Historical database cohort study addressing the clinical patterns prior to idiopathic pulmonary fibrosis (IPF) diagnosis in UK primary care. Issue 5 (30th May 2020) - Thickett, David; Voorham, Jaco; Ryan, Ronan; Jones, Rupert; Coker, Robina; Wilson, Andrew M; Yang, Sen; Ow, Mandy YL; Raju, Priyanka; Chaudhry, Isha; Hardjojo, Antony; Carter, Victoria; et al.
Abstract : Objective: To explore the clinical pathways, including signs and symptoms, and symptom progression patterns preceding idiopathic pulmonary fibrosis (IPF) diagnosis. Design and setting: A historical cohort study was conducted using primary care patient records from the Optimum Patient Care Research Database. Participants: Patients included were at least 30 years, had IPF diagnosis, identified via clinical-coding and free-text records and had a consultation with a chest specialist prior to IPF diagnosis. Outcome measures: The signs and symptoms in the year prior to IPF diagnosis from clinical codes and free-text in primary care electronic records included: cough, dyspnoea, dry cough, weight loss, fatigue/malaise, loss of appetite, crackles and clubbed fingers. The time course of presentations of clinical features and investigations in the years prior to IPF diagnosis were mapped. Results: Within 462 patients identified, the majority (77.9%) had a respiratory consultation within 365 days prior to the chest specialist visit preceding the IPF diagnosis recorded in their primary care records. The most common symptoms recorded in the 1 year prior to IPF diagnosis were dyspnoea (48.7%) and cough (40.9%); other signs and symptoms were rarely recorded (<5%). The majority of patients with cough (58.0%) and dyspnoea (55.0%) in the 1 year before IPF diagnosis had multiple recordings of the respective symptoms. Both cough and dyspnoea were recorded in 23.4% of patients in the year prior to diagnosis. Consultation rates for cough, dyspnoea and both, but not other signs or symptoms, began to increase 4 to 5 years prior diagnosis, with the sharpest increase in the last year. Cough and dyspnoea were often preceded by a reduction in measured weight over 5 years leading to IPF diagnosis. Conclusion: Prolonged cough and/or progressive dyspnoea, especially if accompanied with weight loss, should signal for a referral to specialist assessment at the earliest opportunity.